Vidékgazdaság, kultúra, lokalizáció: eltérő válaszok és fejlődési differenciák - Kis, Krisztián (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Local economic conditions in rural areas are the outcome of processes that are an interplay of local and global forces. In this frame, economic performance of rural regions will depend on local responses, that are determined by the endowment of local resources. Commentators tend to agree that nontraditional (intangible or immaterial) resources are becoming increasingly important in social and economic development takes place in rural areas. An increasing body of literature stresses that local culture, as an intangible resource or capital asset is the major determinant of the pattern pursued by local economies of rural areas. This paper focuses on local culture - and its relation to rural (economic) restructuring - that play a crucial role in responding to the global forces originate from the current globalization process. In this approach, local culture is the major differentiating factor among rural economies, which may facilitate or hinder the rural economy's adaptation to globalization.